2015
DOI: 10.3171/2014.9.peds146
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical treatment of arteriovenous malformations in pediatric patients: the Boston Children's Hospital experience

Abstract: OBJECT Outcomes of microsurgical treatment of arteriovenous malformations (AVMs) in children are infrequently reported across large cohorts. METHODS The authors undertook a retrospective review of departmental and hospital databases to obtain the medical data of all patients up to 18 years of age who were diagnosed with cerebral AVMs. Demographic and AVM angioarchitectural characteristics were analyzed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 41 publications
3
54
0
Order By: Relevance
“…In our pediatric cases, 42–46% of children were severely disabled after hemorrhagic presentation or subsequent hemorrhage, which is congruent with previous data of treated pediatric bAVM series (32–50%) [5, 6]. While some previous reports on bAVM patients of all ages suggested a lower rate of severe disability after incident hemorrhage (3–45%), however, a longer delay between bAVM rupture and neurological assessment might be one of the factors for the prevalence of lower rates in those studies (Table 4) [3, 18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our pediatric cases, 42–46% of children were severely disabled after hemorrhagic presentation or subsequent hemorrhage, which is congruent with previous data of treated pediatric bAVM series (32–50%) [5, 6]. While some previous reports on bAVM patients of all ages suggested a lower rate of severe disability after incident hemorrhage (3–45%), however, a longer delay between bAVM rupture and neurological assessment might be one of the factors for the prevalence of lower rates in those studies (Table 4) [3, 18].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, treatment-free time after hemorrhage varies between individuals, further hindering the comparison of clinical outcome. A recent study indicated that although intervention would change bAVM prognosis, the long-term outcome was still correlated with neurological function at presentation [6]. In addition, neurological evaluation immediately after the index event was more likely to reveal the actual impact of hemorrhage after bAVM rupture [3].…”
Section: Introductionmentioning
confidence: 99%
“…1,15 In some instances, especially deep-seated and cortical eloquent lesions, surgery may carry excessive risks of morbidity, and less invasive methods are required. 1,2,13 Although SRS is often recommended, this technique needs a latency period of 2 to 3 years in which hemorrhage may occur. 3,11,16 Additionally, long-term effects of ionizing radiation in the developing brain are not fully determined, and the efficacy of SRS in high-flow arteriovenous fistulae is not well documented.…”
Section: Discussion Natural History and Treatment Paradigmmentioning
confidence: 99%
“…[1][2][3] In this age group, these lesions present an aggressive clinical course with higher rates of hemorrhage and mortality compared with adults. 3 Consequently, several publications have addressed that lifetime risks of critical intracranial hemorrhage in conjunction with the ability of the pediatric nervous system to recover from injury underscores risks of aggressive therapy.…”
mentioning
confidence: 97%
“…Nonetheless, a review of the ARUBA study is relevant, as its data reveal an annual stroke rate of approximately 4% for untreated AVMs [7].…”
Section: Discussionmentioning
confidence: 99%